Direct Shear Test of Unsaturated Soil (2017)
The present study focuses on some tentative laboratory tests using a newly-constructed modified direct shear test apparatus. The single-stage and multistage direct shear tests were performed to determine the shear rate and test scheme of unsaturated shear test. Shear strength parameters of unsaturated soil in different conditions are obtained and the tests indicate good agreement with typical theories of unsaturated soil, the nonlinear matric suction failure envelope is determined. Some shear strength equations are also fitted through the experimental results.